1990
DOI: 10.1126/science.2321026
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse-Double Layer at a Membrane-Aqueous Interface Measured with X-Ray Standing Waves

Abstract: The ion distribution in an electrolyte solution in contact with a charged polymerized phospholipid membrane was directly measured with long-period x-ray standing waves. The 27-angstrom-thick lipid monolayer was supported on a tungsten/silicon mirror. X-ray standing waves were generated above the mirror surface by total external reflection of a 9.8-kiloelectron volt x-ray beam from a synchrotron undulator. The membrane surface, which contained negatively charged phosphate headgroups, was bathed in a dilute ZnCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
133
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(137 citation statements)
references
References 13 publications
4
133
0
Order By: Relevance
“…Important areas of combined SR and multilayer applications are projection and contact x-ray microscopy in the \water window" range ( ¶ = 2.35 { 4.5 nm) [1], X-ray spectroscopy and microscopy using BraggFresnel elements [2,3]. Best quality multilayer mirrors have been used as generators of X-ray standing waves for investigation of structural properties of Blodgett-Langmuir lms [4][5][6]. Extreme ultraviolet (EUV) projection lithography in the 13 nm spectral region using both pulse plasma and SR sources seems to be potentially the largest application eld for multilayer developments [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Important areas of combined SR and multilayer applications are projection and contact x-ray microscopy in the \water window" range ( ¶ = 2.35 { 4.5 nm) [1], X-ray spectroscopy and microscopy using BraggFresnel elements [2,3]. Best quality multilayer mirrors have been used as generators of X-ray standing waves for investigation of structural properties of Blodgett-Langmuir lms [4][5][6]. Extreme ultraviolet (EUV) projection lithography in the 13 nm spectral region using both pulse plasma and SR sources seems to be potentially the largest application eld for multilayer developments [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This principle has been exploited for the study of interfacial phenomena involving solid, liquid, and gas phases (8)(9)(10)(11)(12)(13)(14)(15)(16). High resolution perpendicular to the interface is implied by SWXF experiments in Bragg reflection configuration, in which case planar, nanometric multilayers are used to create strongly modulated standing waves above the terminal surface close to the Bragg condition (9,10). However, such high-resolution studies have thus far dealt only with the fluorescence of comparatively heavy elements.…”
mentioning
confidence: 99%
“…For a layer of fluorescing atoms at a fixed position z, the fluorescent intensity is proportional to the standing wave intensity at the atom layer position (26). For a diffuse or continuous metal distribution, which we assume for our experiments, the net fluorescence yield, Y( ), is given by (24,27,28) Y͑ ͒ ϰ ͵ N͑z͒ I͑z, ͒dz,…”
mentioning
confidence: 99%
“…Previous studies have shown the utility of the long-period XSW technique for determining the spatial distribution of heavy metal ions within a variety of organic thin films and model membranes formed on mirror surfaces (23)(24)(25). Long-period XSWs are generated from the interference between an incident and reflected x-ray beam at incident angles below the critical angle for total external reflection of the substrate (Ϸ160 mdeg and 180 mdeg for ␣-Al 2 O 3 and ␣-Fe 2 O 3 , at 14 keV) (Fig.…”
mentioning
confidence: 99%